Refictionalizing cruelty: dramatization and travesty in Pedro Lemebel’s Tengo miedo torero - Pérez Guerrero, Cristian (Revista Chilena de Literatura, 2019)
In dictatorship, the transvestite must survive as a sexually different subject and as a subject thrown into a cruel historical moment. For this reason, Tengo miedo torero is the narrative space where the author can build a battlefield that alienates the Loca del Frente of its context. This is done through the hyped dramatization of spaces and characters, and through the travesty of violent actions presented. Thus, both routes of escape build a re-fictionalization of the story told.